Ökologisch-phaenologische Forschungen über Thysanopteren. Zur Kenntnis der Thysanopterenfauna der Karpathen (Thysanoptera). - Knechtel, Wilhelm Karl (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are published the author’s results of the investigation of the Thysanopterous fauna of a natural lawn at the altitude of the spruce (Picetum excelsae) at "Piatra-Arsa" (Bucegimountains). These investigations were based upon the seasonal development of the flora, the interspecific appearence, and the population density of Thysanoptera found in the inflorescences of the respective plant species.